Analisis Survival dengan Model Regresi pada Data Tersensor Berdistribusi Log-Logistik - Gatri Eka Kusumawardhani; Vera Maya Santi; Suyono Suyono (Program Studi Statistika FMIPA UNJ, 2018)
Survival analysis is an analysis used to determine the length of time required by an object in order to survive. That time is sometimes influenced by several factors called independent variables. One way to know relationship is through a regression model. The dependent variable in this regression model is a survival time which is log-logistic distributed. The data used in this study were right censored survival data. Log-logistic regression models for survival data can be expressed by transformation Y=lnT= Î¸0+Î¸1xi1+...+Î¸ixij+ÏƒÔ‘. The parameter of the log-logistic regression models for right censored survival data are estimated with the maximum likelihood method. In this study, the application of log-logistic regression model for survival data is in data of lung cancer patients. Based on the data already performed, best log-logistic regression model is obtained yi=1.92458+0.0242393 xi1+0.639037Ô‘i.